Evaluation of elite breeding lines of flue-cured tobacco for field and market performance - Roux, Carl Z. (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Sustainable Plant-Genetic Resource Management))--University of Pretoria, 2006.